GEREJA MEMPERSIAPKAN PEMUDA MELALUI MENTORING DI GBI ASIA AFRIKA BANDUNG - Robert William Rungkat; Joko Prihanto (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2021)
Abstract With the progress of the changing times, making all things in this world experience significant changes, even the church did not escape from these challenges. But the most striking problem in the end times is the lack of the church to prepare the younger generation or youth for the future. Because the younger generation is the future of the church. The church forgetting the younger generation is the same as forgetting the future of the church itself. Therefore, the author here is interested in further researching how the church prepares itself for the future by mentoring youth so that the church has a bright future and is maintained according to God's will? And what the author has researched, is practiced in the Bethel Church of Indonesia Asia Africa (Kalam Hidup) Bandung to prove whether youth mentoring can answer previous questions at GBI Asia Afrika (Kalam Hidup) Bandung?